2020
DOI: 10.1177/0363546520960461
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Values for Success After Hip Arthroscopy Using the Patient-Reported Outcomes Measurement Information System Assessment: Determining the Minimum Clinically Important Difference and Patient Acceptable Symptomatic State

Abstract: Background: Threshold values for patient-reported outcome measures, such as the minimum clinically important difference (MCID) and patient acceptable symptomatic state (PASS), are important for relating postoperative outcomes to meaningful functional improvement. Purpose: To determine the PASS and MCID after hip arthroscopy for femoroacetabular impingement using the Patient-Reported Outcomes Measurement Information System (PROMIS) questionnaire. Study Design: Cohort study (diagnosis); Level of evidence, 3. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Previous studies have, with relevant outcome measures for CIDP such as grip strength, 2-minute walk test, or Timed Up and Go test, attempted to determine the MDC in limited numbers of subjects with type 2 diabetes 12 and total hip arthroplasty. 13 MID has similarly been evaluated in subjects with diverse conditions such as after hip arthroplasty 14 or chronic obstructive pulmonary disease. 15 One of the important questions in the assessment of subjects with CIDP is the reliability of patient-reported subjective improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have, with relevant outcome measures for CIDP such as grip strength, 2-minute walk test, or Timed Up and Go test, attempted to determine the MDC in limited numbers of subjects with type 2 diabetes 12 and total hip arthroplasty. 13 MID has similarly been evaluated in subjects with diverse conditions such as after hip arthroplasty 14 or chronic obstructive pulmonary disease. 15 One of the important questions in the assessment of subjects with CIDP is the reliability of patient-reported subjective improvement.…”
Section: Introductionmentioning
confidence: 99%
“…40 MCIDs for PROMIS measures in the hip population are less established, but likely only the PROMIS Pediatric Pain Interference and Mobility measures were meaningfully worse in the surgical cohort (before adjusting for other variables). [41][42][43] Regarding radiographic measurements, maximum α angle was only a predictor of progression to surgery for patients with severe radiographic cam FAI, possibly because patients' true FAI morphology is not completely captured on two-dimensional radiographs and/or because patients' activities, movement patterns, and other variables play a meaningful role in the responsiveness of structural FAI morphology to conservative management. 14,44,45 This modest association between α angle and clinical course is consistent with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of this expansion, it is important to keep in mind that defining clinically significant outcomes using CIOVs lends itself to variable interpretation depending on which values are used as well as which methodology was employed to arrive to the values (e.g., anchor-based vs. distribution-based calculation of MCID). For PROMIS-PF and PROMIS-PI, multiple MCID 32,33,44 and PASS 32,33 values have been reported. To ensure the most certain interpretation of our results based on the available literature, we ultimately decided to use the CIOV values of Kuhns et al because, to our knowledge, they were the highest threshold values reported in the hip arthroscopy literature for PROMIS-PF and PROMIS-PI.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, the postop PROMIS-PF and PROMIS-PI scores for each patient were characterized based on whether they surpassed PASS threshold values as described by Kuhns et al (51.8 for PROMIS-PF, 51.9 for PROMIS-PI). 32 Achieving any of these CIOV values was interpreted as a clinically favorable outcome. 32,33,43 Secondary outcomes included complications and revision surgeries, which were extracted from the EMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation